A polymer solid electrolyte doped with strontium titanate nanowires and a preparation method thereof
By using polymer solid electrolyte doped with strontium titanate nanowires in lithium-ion batteries, the safety hazards and low conductivity of traditional electrolytes are solved, and higher ionic conductivity and better stability and safety are achieved sex.
Patent Information
- Application Number
- CN202010806646.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-08-12
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2040-08-12
AI Technical Summary
The organic liquid electrolytes used in traditional lithium-ion batteries have safety risks of fire and explosion, while the solid electrolyte has a low ionic conductivity, which limits its application in lithium-ion batteries.
The polymer solid electrolyte doped with strontium titanate nanowires were prepared by two-step hydrothermal method, and added it to the PEO-PVAC polymer, and the electrolyte film was prepared by solution casting and hot pressing treatment.
The ionic conductivity of solid electrolyte is improved, its thermal stability, interface stability and safety performance are enhanced, and the room temperature ionic conductivity is 8.8×10-4S/cm.
Smart Images

Figure CN111987352B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery preparation, and in particular to a polymer solid electrolyte doped with strontium titanate nanowires and a preparation method thereof. Background Art
[0002] Traditional lithium-ion batteries mostly use volatile and flammable organic liquid electrolytes, which pose safety hazards such as fire and even explosion. Replacing liquid electrolytes with solid electrolytes can ensure the safety of lithium-ion batteries, inhibit the formation of lithium dendrites, and improve the energy density of batteries. However, the ionic conductivity of solid electrolytes is several orders of magnitude lower than that of liquid electrolytes, which greatly limits their practical application in lithium-ion batteries. Solid electrolytes are generally divided into inorganic and organic polymer solid electrolytes. Compared with inorganic solid electrolytes, organic polymer solid electrolytes composed of polymer matrix and conductive lithium salts are light, flexible, highly thermally stable, and compatible with electrodes. The preparation process is simple and has good application prospects. PEO-based polymer electrolytes are the most widely studied and most promising polymer electrolyte system for large-scale commercial production. However, the room temperature crystallinity of the PEO matrix is high (60-70%) and the room temperature ionic conductivity is low, so it is not suitable for direct use as an electrolyte. To this end, domestic and foreign researchers have adopted a variety of modification methods to enhance the conductive properties of the system, mainly including the addition of plasticizers, copolymerization, blending, and the addition of inorganic fillers. Among them, the blending technology is simple and effective, and has great potential in actual production. At the same time, the addition of inorganic fillers such as Al2O3, SiO2, TiO2 and ZrO2 helps to synergistically improve the mechanical strength and ionic conductivity of PEO-based polymer electrolyte materials. However, since these inorganic fillers are mainly added in the form of particles, lithium ions must pass through the numerous connection points between these particle fillers during transmission, resulting in limited improvement in ionic conductivity. Summary of the invention
[0003] In order to solve the above problems, the purpose of the present invention is to provide a polymer solid electrolyte doped with strontium titanate nanowires and a preparation method thereof. The polymer solid electrolyte doped with strontium titanate nanowires obtained by the present invention has good ionic conductivity, interface stability, mechanical stability and good thermal stability.
[0004] To achieve the above purpose, the polymer solid electrolyte doped with strontium titanate nanowires designed by the present invention includes a matrix and a lithium salt, wherein the matrix is polyethylene oxide-polyvinyl acetate, and the lithium salt is lithium bistrifluoromethanesulfonyl imide. It is characterized in that it also includes a one-dimensional inorganic filler, which is a strontium titanate nanowire, and the aspect ratio of the strontium titanate nanowire is 20 to 40.
[0005] As a preferred embodiment, the polymer solid electrolyte doped with strontium titanate nanowires is prepared from the following components, wherein the weight proportions of each component are: 50-65 parts of polyethylene oxide, 8-25 parts of polyvinyl acetate, 13-15 parts of lithium bis(trifluoromethanesulfonyl)imide and 4-25 parts of strontium titanate nanowires.
[0006] As a preferred embodiment, the polymer solid electrolyte doped with strontium titanate nanowires is prepared from the following components, and the weight proportions of each component are: 50-54 parts of polyethylene oxide, 10-20 parts of polyvinyl acetate, 14-15 parts of lithium bistrifluoromethanesulfonyl imide, and 4-25 parts of strontium titanate nanowires.
[0007] As a preferred embodiment, the polymer solid electrolyte doped with strontium titanate nanowires is prepared from the following components, and the weight proportions of each component are: 54 parts of polyethylene oxide, 20 parts of polyvinyl acetate, 14 parts of lithium bis(trifluoromethanesulfonyl)imide, and 4 parts of strontium titanate nanowires.
[0008] As a preferred embodiment, the viscosity average molecular weight of the polyethylene oxide is 1×10 5 ~1×10 6 ; The viscosity average molecular weight of polyvinyl acetate is 5×10 4 .
[0009] A method for preparing a polymer solid electrolyte doped with strontium titanate nanowires comprises the following steps: firstly preparing the strontium titanate nanowires by a two-step hydrothermal method, then using polyethylene oxide-polyvinyl acetate as a matrix, lithium bistrifluoromethanesulfonyl imide as a lithium salt, and strontium titanate nanowires as fillers, preparing an electrolyte film by a solution casting method and a hot pressing process, and obtaining a polymer solid electrolyte doped with strontium titanate nanowires.
[0010] As a preferred embodiment, the preparation method specifically comprises the steps of:
[0011] (1) Preparation of strontium titanate nanowires: adding titanium dioxide nanoparticles to a sodium hydroxide solution, hydroheating at 160°C to 200°C for 12 to 24 hours, washing the precipitate obtained by the reaction with deionized water, and drying to obtain sodium titanate nanowires; preparing a mixed solution of sodium titanate nanowires and strontium hydroxide octahydrate in a molar ratio of Sr:Ti=3:4 to 1:1, hydroheating at 160°C to 200°C for 4 to 12 hours, washing the reaction product with deionized water and ethanol solution, and drying to obtain strontium titanate nanowires;
[0012] (2) Preparation of composite electrolyte: The obtained strontium titanate nanowires are mixed with an organic solvent acetonitrile, and ultrasonically dispersed for 10 to 30 minutes, and a polymer matrix of polyethylene oxide, polyvinyl acetate and lithium salt of lithium bis(trifluoromethanesulfonyl imide) are added, and stirred for 8 to 12 hours to obtain a translucent viscous sol; the obtained sol is poured into a polytetrafluoroethylene mold, naturally dried, and then vacuum dried at 40 to 60° C. for 12 to 48 hours, and finally hot-pressed to obtain a solid polymer composite electrolyte membrane.
[0013] As a preferred embodiment, in step (2), the weight proportions of the polyethylene oxide, polyvinyl acetate, lithium bis(trifluoromethanesulfonyl imide) and strontium titanate nanowires are 50 to 65 parts of polyethylene oxide, 8 to 25 parts of polyvinyl acetate, 13 to 15 parts of lithium bis(trifluoromethanesulfonyl imide) and 4 to 25 parts of strontium titanate nanowires.
[0014] As a preferred solution, the hot pressing pressure is 5 to 10 MPa, and the holding time is 5 to 10 minutes.
[0015] As a preferred embodiment, in the step (1), the obtained sodium titanate nanowires and polyvinyl alcohol are fully dispersed and then added into the strontium hydroxide octahydrate solution.
[0016] The principle of the present invention is: adding strontium titanate nanowires to PEO-PVAC polymer solid electrolytes. On the one hand, strontium titanate has a high dielectric constant, which can greatly reduce the crystallinity of the polymer, change the chain segment mobility of the system, and improve the ionic conductivity; on the other hand, the strong Lewis acid-base reaction between the electrolyte ions and the surface chemical groups of strontium titanate nanowires promotes the dissociation of metal salts and stabilizes anions, thereby improving ionic conductivity. In addition, strontium titanate nanowires, as one-dimensional inorganic fillers, can provide a more continuous ion conduction path in the electrolyte, thereby improving ionic conductivity.
[0017] The advantages of the present invention are that compared with existing polymer solid electrolytes, the present invention reduces the crystallinity of the polymer by adding one-dimensional strontium titanate nanowires as fillers into the polymer matrix, provides a more continuous ion conduction path, and ultimately improves the ion conductivity of the solid electrolyte.
[0018] Compared with the prior art, the polymer solid electrolyte doped with strontium titanate nanowires prepared by the present invention has good thermal stability, interface stability and safety performance, and high room temperature ionic conductivity of 8.8×10 -4 The preparation process is simple and controllable, and it is easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the XRD pattern of strontium titanate nanowires prepared by a two-step hydrothermal method in Example 1;
[0020] Figure 2 This is a SEM image of strontium titanate nanowires prepared by a two-step hydrothermal method in Example 1;
[0021] Figure 3 is a SEM image of the electrolyte membrane obtained in Example 1;
[0022] Figure 4 The impedance diagram of the solid electrolyte doped with strontium titanate nanowires prepared in Example 1;
[0023] Figure 5 The impedance diagram of the solid electrolyte doped with strontium titanate nanowires prepared in Example 2;
[0024] Figure 6 The impedance diagram of the solid electrolyte doped with strontium titanate nanowires prepared in Example 3;
[0025] Figure 7 The impedance diagram of the solid electrolyte doped with strontium titanate nanowires prepared in Example 4;
[0026] Figure 8 This is the impedance diagram of the solid electrolyte doped with strontium titanate nanowires prepared in Example 5. DETAILED DESCRIPTION
[0027] In order to better understand the present invention, the present invention will be described in detail below with reference to the accompanying drawings and specific examples.
[0028] Example 1
[0029] A method for preparing a polymer solid electrolyte doped with strontium titanate nanowires comprises the following steps:
[0030] (1) Preparation of strontium titanate nanowires: Prepare a sodium hydroxide aqueous solution with a concentration of 10 mol / L, add 1 g of nano-titanium dioxide, stir evenly to obtain a suspension, transfer the prepared suspension to a hydrothermal reactor, place it at 180°C for hydrothermal reaction for 12 hours, then wash the precipitate obtained by the reaction with deionized water and dry it to obtain sodium titanate nanowire powder, add the sodium titanate nanowire to 1 mol / L strontium hydroxide octahydrate under stirring, wherein the molar ratio of sodium titanate nanowire to strontium hydroxide octahydrate is 3:4, stir evenly to obtain a precursor solution, transfer the obtained precursor solution to a hydrothermal reactor, place it at 180°C for hydrothermal reaction for 4 hours, wash the reaction product with deionized water and ethanol solution, and dry it to obtain strontium titanate nanowire powder; combine Figure 1 and Figure 2 As shown, the XRD and SEM images of strontium titanate nanowires prepared by a two-step hydrothermal method have an aspect ratio of 20 to 40.
[0031] (2) Preparation of composite electrolyte: 0.14 g of lithium bis(trifluoromethanesulfonyl)imide LiTFSI powder, 0.54 g of polyethylene oxide PEO powder, 0.20 g of poly(vinyl acetate) PVAC and 0.04 g of strontium titanate nanowire powder were weighed. The molecular weight of the PEO powder used was 1×10 6 The molecular weight of PVAC powder is 5×10 4 . The vacuum-dried lithium bis(trifluoromethanesulfonyl)imide powder was placed in an acetonitrile solution and mechanically stirred for 20 minutes until completely dissolved. Then, the dried strontium titanate nanowire powder was added to the evenly mixed solution. After ultrasonic dispersion for 30 minutes, it was completely dispersed in the solution under mechanical stirring. Finally, the dried polyethylene oxide and polyvinyl acetate were added and stirred for 12 hours to form a uniform suspension. The obtained suspension was introduced into a polytetrafluoroethylene mold by casting, dried at room temperature for 4 to 8 hours, and then placed in a vacuum drying oven and dried at 40°C for 48 hours to form a film. After peeling, it was hot pressed at a temperature of 45°C and a pressure of 10MPa for 10 minutes to obtain the following. Figure 3 The uniform composite electrolyte membrane shown, combined with Figure 4 As shown, its ionic conductivity is 8.8×10 -4 S / cm.
[0032] Example 2
[0033] A method for preparing a polymer solid electrolyte doped with strontium titanate nanowires comprises the following steps:
[0034] (1) Preparation of strontium titanate nanowires: Prepare a sodium hydroxide aqueous solution with a concentration of 10 mol / L, add 1 g of nano-titanium dioxide, stir evenly to obtain a suspension, transfer the prepared suspension to a hydrothermal reactor, place it at 180°C for hydrothermal reaction for 12 hours, and then wash the precipitate obtained by the reaction with deionized water and dry it to obtain sodium titanate nanowire powder. Add sodium titanate nanowires to 1 mol / L strontium hydroxide octahydrate under stirring, wherein the molar ratio of sodium titanate nanowires to strontium hydroxide octahydrate is 1:1, stir evenly to obtain a precursor solution, transfer the obtained precursor solution to a hydrothermal reactor, place it at 180°C for hydrothermal reaction for 4 hours, wash the reaction product with deionized water and ethanol solution, and dry it to obtain strontium titanate nanowire powder.
[0035] (2) Preparation of composite electrolyte: 0.14 g of lithium bis(trifluoromethanesulfonyl)imide LiTFSI powder, 0.55 g of polyethylene oxide PEO powder, 0.20 g of poly(vinyl acetate) PVAC and 0.09 g of strontium titanate nanowire powder were weighed. The molecular weight of the PEO powder used was 1×10 6 The molecular weight of PVAC powder is 5×10 4. The vacuum-dried lithium bis(trifluoromethanesulfonyl)imide powder was placed in an acetonitrile solution and mechanically stirred for 20 minutes until completely dissolved. Then, the dried strontium titanate nanowire powder was added to the evenly mixed solution. After ultrasonic dispersion for 30 minutes, it was completely dispersed in the solution under mechanical stirring. Finally, the dried polyethylene oxide and polyvinyl acetate were added and stirred for 12 hours to form a uniform suspension. The obtained suspension was introduced into a polytetrafluoroethylene mold by casting, dried at room temperature for 4 to 8 hours, and then placed in a vacuum drying oven and dried at 40°C for 48 hours to form a film. After peeling, it was hot-pressed at a temperature of 45°C and a pressure of 10MPa for 10 minutes to obtain a uniform composite electrolyte membrane. Figure 5 As shown, its ionic conductivity is 1.0×10 -4 S / cm.
[0036] Example 3
[0037] A method for preparing a polymer solid electrolyte doped with strontium titanate nanowires comprises the following steps:
[0038] (1) Preparation of strontium titanate nanowires: Prepare a sodium hydroxide aqueous solution with a concentration of 10 mol / L, add 1 g of nano-titanium dioxide, stir evenly to obtain a suspension, transfer the prepared suspension to a hydrothermal reactor, place it at 180°C for hydrothermal reaction for 12 hours, and then wash the precipitate obtained by the reaction with deionized water and dry it to obtain sodium titanate nanowire powder. Add sodium titanate nanowires to 1 mol / L strontium hydroxide octahydrate under stirring, wherein the molar ratio of sodium titanate nanowires to strontium hydroxide octahydrate is 4:5, stir evenly to obtain a precursor solution, transfer the obtained precursor solution to a hydrothermal reactor, place it at 180°C for hydrothermal reaction for 4 hours, wash the reaction product with deionized water and ethanol solution, and dry it to obtain strontium titanate nanowire powder.
[0039] (2) Preparation of composite electrolyte: 0.14 g of lithium bis(trifluoromethanesulfonyl)imide LiTFSI powder, 0.55 g of polyethylene oxide PEO powder, 0.20 g of poly(vinyl acetate) PVAC and 0.18 g of strontium titanate nanowire powder were weighed. The molecular weight of the PEO powder used was 1×10 6 The molecular weight of PVAC powder is 5×10 4. The vacuum-dried lithium bis(trifluoromethanesulfonyl)imide powder was placed in an acetonitrile solution and mechanically stirred for 20 minutes until completely dissolved. Then, the dried strontium titanate nanowire powder was added to the evenly mixed solution. After ultrasonic dispersion for 30 minutes, it was completely dispersed in the solution under mechanical stirring. Finally, the dried polyethylene oxide and polyvinyl acetate were added and stirred for 12 hours to form a uniform suspension. The obtained suspension was introduced into a polytetrafluoroethylene mold by casting, dried at room temperature for 4 to 8 hours, and then placed in a vacuum drying oven and dried at 40°C for 48 hours to form a film. After peeling, it was hot-pressed at a temperature of 45°C and a pressure of 10MPa for 10 minutes to obtain a uniform composite electrolyte membrane. Figure 6 As shown, its ionic conductivity is 1.1×10 -4 S / cm.
[0040] Example 4
[0041] A method for preparing a polymer solid electrolyte doped with strontium titanate nanowires comprises the following steps:
[0042] (1) Preparation of strontium titanate nanowires: Prepare a sodium hydroxide aqueous solution with a concentration of 10 mol / L, add 1 g of nano-titanium dioxide, stir evenly to obtain a suspension, transfer the prepared suspension to a hydrothermal reactor, place it at 180°C for hydrothermal reaction for 12 hours, and then wash the precipitate obtained by the reaction with deionized water and dry it to obtain sodium titanate nanowire powder. Add sodium titanate nanowires to 1 mol / L strontium hydroxide octahydrate under stirring, wherein the molar ratio of sodium titanate nanowires to strontium hydroxide octahydrate is 1:1, stir evenly to obtain a precursor solution, transfer the obtained precursor solution to a hydrothermal reactor, place it at 180°C for hydrothermal reaction for 8 hours, wash the reaction product with deionized water and ethanol solution, and dry it to obtain strontium titanate nanowire powder.
[0043] (2) Preparation of composite electrolyte: 0.14 g of lithium bis(trifluoromethanesulfonyl)imide LiTFSI powder, 0.54 g of polyethylene oxide PEO powder, 0.10 g of poly(vinyl acetate) PVAC and 0.06 g of strontium titanate nanowire powder were weighed. The molecular weight of the PEO powder used was 1×10 6 The molecular weight of PVAC powder is 5×10 4. The vacuum-dried lithium bis(trifluoromethanesulfonyl)imide powder was placed in an acetonitrile solution and mechanically stirred for 20 minutes until completely dissolved. Then, the dried strontium titanate nanowire powder was added to the evenly mixed solution. After ultrasonic dispersion for 30 minutes, it was completely dispersed in the solution under mechanical stirring. Finally, the dried polyethylene oxide and polyvinyl acetate were added and stirred for 12 hours to form a uniform suspension. The obtained suspension was introduced into a polytetrafluoroethylene mold by casting, dried at room temperature for 4 to 8 hours, and then placed in a vacuum drying oven and dried at 40°C for 48 hours to form a film. After peeling, it was hot-pressed at a temperature of 45°C and a pressure of 10MPa for 10 minutes to obtain a uniform composite electrolyte membrane. Figure 7 As shown, its ionic conductivity is 2.6×10 -4 S / cm.
[0044] Example 5
[0045] A method for preparing a polymer solid electrolyte doped with strontium titanate nanowires comprises the following steps:
[0046] (1) Preparation of strontium titanate nanowires: Prepare a sodium hydroxide aqueous solution with a concentration of 10 mol / L, add 1 g of nano-titanium dioxide, stir evenly to obtain a suspension, transfer the prepared suspension to a hydrothermal reactor, place it at 180°C for hydrothermal reaction for 12 hours, and then wash the precipitate obtained by the reaction with deionized water and dry it to obtain sodium titanate nanowire powder. Sodium titanate nanowires and 2 g / L polyvinyl alcohol PVA are added to 1 mol / L strontium hydroxide octahydrate under stirring, wherein the molar ratio of sodium titanate nanowires to strontium hydroxide octahydrate is 1:1, stir evenly to obtain a precursor solution, transfer the obtained precursor solution to a hydrothermal reactor, place it at 180°C for hydrothermal reaction for 4 hours, wash the reaction product with deionized water and ethanol solution, and dry it to obtain strontium titanate nanowire powder.
[0047] (2) Preparation of composite electrolyte: 0.14 g of lithium bis(trifluoromethanesulfonyl)imide LiTFSI powder, 0.54 g of polyethylene oxide PEO powder, 0.10 g of poly(vinyl acetate) PVAC and 0.24 g of strontium titanate nanowire powder were weighed. The molecular weight of the PEO powder used was 1×10 6 The molecular weight of PVAC powder is 5×10 4. The vacuum-dried lithium bis(trifluoromethanesulfonyl)imide powder was placed in an acetonitrile solution and mechanically stirred for 20 minutes until completely dissolved. Then, the dried strontium titanate nanowire powder was added to the evenly mixed solution. After ultrasonic dispersion for 30 minutes, it was completely dispersed in the solution under mechanical stirring. Finally, the dried polyethylene oxide and polyvinyl acetate were added and stirred for 12 hours to form a uniform suspension. The obtained suspension was introduced into a polytetrafluoroethylene mold by casting, dried at room temperature for 4 to 8 hours, and then placed in a vacuum drying oven and dried at 40°C for 48 hours to form a film. After peeling, it was hot-pressed at a temperature of 45°C and a pressure of 10MPa for 10 minutes to obtain a uniform composite electrolyte membrane. Figure 8 As shown, its ionic conductivity is 3.2×10 -4 S / cm.
[0048] Example 6
[0049] A method for preparing a polymer solid electrolyte doped with strontium titanate nanowires comprises the following steps:
[0050] (1) Preparation of strontium titanate nanowires: Prepare a sodium hydroxide aqueous solution with a concentration of 10 mol / L, add 1 g of nano-titanium dioxide, stir evenly to obtain a suspension, transfer the prepared suspension to a hydrothermal reactor, place it at 180°C for hydrothermal reaction for 12 hours, and then obtain sodium titanate nanowire powder through subsequent treatment. Sodium titanate nanowires and 2 g / L polyvinyl alcohol PVA are added to 1 mol / L strontium hydroxide octahydrate under stirring, wherein the molar ratio of sodium titanate nanowires to strontium hydroxide octahydrate is 1:1, stir evenly to obtain a precursor solution, transfer the obtained precursor solution to a hydrothermal reactor, place it at 180°C for hydrothermal reaction for 4 hours, and obtain strontium titanate nanowire powder through subsequent treatment.
[0051] (2) Preparation of composite electrolyte: 0.13 g of lithium bis(trifluoromethanesulfonyl)imide LiTFSI powder, 0.50 g of polyethylene oxide PEO powder, 0.10 g of poly(vinyl acetate) PVAC and 0.20 g of strontium titanate nanowire powder were weighed. The molecular weight of the PEO powder used was 1×10 6 The molecular weight of PVAC powder is 5×10 4. The vacuum-dried lithium bis(trifluoromethanesulfonyl)imide powder was placed in an acetonitrile solution and mechanically stirred for 20 minutes until it was completely dissolved. Then, the dried strontium titanate nanowire powder was added to the mixed solution. After ultrasonic dispersion for 30 minutes, it was completely dispersed in the solution under mechanical stirring. Finally, the dried polyethylene oxide and polyvinyl acetate were added and stirred for 12 hours to form a uniform suspension. The obtained suspension was introduced into a polytetrafluoroethylene mold by casting, dried at room temperature for 4 to 8 hours, and then placed in a vacuum drying oven at 40°C for 48 hours to form a film. After peeling, it was hot-pressed at a temperature of 45°C and a pressure of 10MPa for 10 minutes to obtain a uniform composite electrolyte membrane with an ionic conductivity of 3.6×10 -4 S / cm.
[0052] Example 7
[0053] A method for preparing a polymer solid electrolyte doped with strontium titanate nanowires comprises the following steps:
[0054] (1) Preparation of strontium titanate nanowires: Prepare a sodium hydroxide aqueous solution with a concentration of 10 mol / L, add 1 g of nano-titanium dioxide, stir evenly to obtain a suspension, transfer the prepared suspension to a hydrothermal reactor, place it at 180°C for hydrothermal reaction for 12 hours, and then obtain sodium titanate nanowire powder through subsequent treatment. Sodium titanate nanowires and 2 g / L polyvinyl alcohol PVA are added to 1 mol / L strontium hydroxide octahydrate under stirring, wherein the molar ratio of sodium titanate nanowires to strontium hydroxide octahydrate is 1:1, stir evenly to obtain a precursor solution, transfer the obtained precursor solution to a hydrothermal reactor, place it at 180°C for hydrothermal reaction for 4 hours, and obtain strontium titanate nanowire powder through subsequent treatment.
[0055] (2) Preparation of composite electrolyte: 0.15 g of lithium bis(trifluoromethanesulfonyl)imide LiTFSI powder, 0.65 g of polyethylene oxide PEO powder, 0.08 g of poly(vinyl acetate) PVAC and 0.07 g of strontium titanate nanowire powder were weighed. The molecular weight of the PEO powder used was 1×10 6 The molecular weight of PVAC powder is 5×10 4 . The vacuum-dried lithium bis(trifluoromethanesulfonyl)imide powder was placed in an acetonitrile solution and mechanically stirred for 20 minutes until it was completely dissolved. Then, the dried strontium titanate nanowire powder was added to the mixed solution. After ultrasonic dispersion for 30 minutes, it was completely dispersed in the solution under mechanical stirring. Finally, the dried polyethylene oxide and polyvinyl acetate were added and stirred for 12 hours to form a uniform suspension. The obtained suspension was introduced into a polytetrafluoroethylene mold by casting, dried at room temperature for 4 to 8 hours, and then placed in a vacuum drying oven at 40°C for 48 hours to form a film. After peeling, it was hot pressed at a temperature of 45°C and a pressure of 5MPa for 10 minutes to obtain a uniform composite electrolyte membrane with an ionic conductivity of 1.2×10-4 S / cm.
[0056] Example 8
[0057] A method for preparing a polymer solid electrolyte doped with strontium titanate nanowires comprises the following steps:
[0058] (1) Preparation of strontium titanate nanowires: Prepare a sodium hydroxide aqueous solution with a concentration of 10 mol / L, add 1 g of nano-titanium dioxide, stir evenly to obtain a suspension, transfer the prepared suspension to a hydrothermal reactor, place it at 180°C for hydrothermal reaction for 12 hours, and then obtain sodium titanate nanowire powder through subsequent treatment. Sodium titanate nanowires and 2 g / L polyvinyl alcohol PVA are added to 1 mol / L strontium hydroxide octahydrate under stirring, wherein the molar ratio of sodium titanate nanowires to strontium hydroxide octahydrate is 1:1, stir evenly to obtain a precursor solution, transfer the obtained precursor solution to a hydrothermal reactor, place it at 180°C for hydrothermal reaction for 4 hours, and obtain strontium titanate nanowire powder through subsequent treatment.
[0059] (2) Preparation of composite electrolyte: 0.14 g of lithium bis(trifluoromethanesulfonyl)imide LiTFSI powder, 0.60 g of polyethylene oxide PEO powder, 0.25 g of poly(vinyl acetate) PVAC and 0.08 g of strontium titanate nanowire powder were weighed. The molecular weight of the PEO powder used was 1×10 6 The molecular weight of PVAC powder is 5×10 4 . The vacuum-dried lithium bis(trifluoromethanesulfonyl)imide powder was placed in an acetonitrile solution and mechanically stirred for 20 minutes until it was completely dissolved. Then, the dried strontium titanate nanowire powder was added to the mixed solution. After ultrasonic dispersion for 30 minutes, it was completely dispersed in the solution under mechanical stirring. Finally, the dried polyethylene oxide and polyvinyl acetate were added and stirred for 12 hours to form a uniform suspension. The obtained suspension was introduced into a polytetrafluoroethylene mold by casting, dried at room temperature for 4 to 8 hours, and then placed in a vacuum drying oven at 40°C for 48 hours to form a film. After peeling, it was hot-pressed at a temperature of 45°C and a pressure of 8MPa for 10 minutes to obtain a uniform composite electrolyte membrane with an ionic conductivity of 2.3×10 -4 S / cm.
[0060] Example 9
[0061] A method for preparing a polymer solid electrolyte doped with strontium titanate nanowires comprises the following steps:
[0062] (1) Preparation of strontium titanate nanowires: Prepare a sodium hydroxide aqueous solution with a concentration of 10 mol / L, add 1 g of nano-titanium dioxide, stir evenly to obtain a suspension, transfer the prepared suspension to a hydrothermal reactor, place it at 180°C for hydrothermal reaction for 12 hours, and then obtain sodium titanate nanowire powder through subsequent treatment. Sodium titanate nanowires and 2 g / L polyvinyl alcohol PVA are added to 1 mol / L strontium hydroxide octahydrate under stirring, wherein the molar ratio of sodium titanate nanowires to strontium hydroxide octahydrate is 1:1, stir evenly to obtain a precursor solution, transfer the obtained precursor solution to a hydrothermal reactor, place it at 180°C for hydrothermal reaction for 4 hours, and obtain strontium titanate nanowire powder through subsequent treatment.
[0063] (2) Preparation of composite electrolyte: 0.15 g of lithium bis(trifluoromethanesulfonyl)imide LiTFSI powder, 0.50 g of polyethylene oxide PEO powder, 0.10 g of poly(vinyl acetate) PVAC and 0.25 g of strontium titanate nanowire powder were weighed. The molecular weight of the PEO powder used was 1×10 6 The molecular weight of PVAC powder is 5×10 4 . The vacuum-dried lithium bis(trifluoromethanesulfonyl)imide powder was placed in an acetonitrile solution and mechanically stirred for 20 minutes until it was completely dissolved. Then, the dried strontium titanate nanowire powder was added to the mixed solution. After ultrasonic dispersion for 30 minutes, it was completely dispersed in the solution under mechanical stirring. Finally, the dried polyethylene oxide and polyvinyl acetate were added and stirred for 12 hours to form a uniform suspension. The obtained suspension was introduced into a polytetrafluoroethylene mold by casting, dried at room temperature for 4 to 8 hours, and then placed in a vacuum drying oven at 40°C for 48 hours to form a film. After peeling, it was hot-pressed at a temperature of 45°C and a pressure of 8MPa for 10 minutes to obtain a uniform composite electrolyte membrane with an ionic conductivity of 3.9×10 -4 S / cm.
[0064] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a polymer solid electrolyte doped with strontium titanate nanowires, characterized in that: The method comprises the following steps: firstly preparing strontium titanate nanowires by a two-step hydrothermal method, then using polyethylene oxide-polyvinyl acetate as a matrix, lithium bistrifluoromethanesulfonyl imide as a lithium salt, and strontium titanate nanowires as a filler, and preparing an electrolyte film by a solution casting method and a hot pressing process to obtain a polymer solid electrolyte doped with strontium titanate nanowires; The preparation method specifically comprises the steps of: (1) Preparation of strontium titanate nanowires: adding titanium dioxide nanoparticles to a sodium hydroxide solution, hydroheating at 160°C to 200°C for 12 to 24 hours, washing the precipitate obtained by the reaction with deionized water, and drying to obtain sodium titanate nanowires; preparing a mixed solution of sodium titanate nanowires and strontium hydroxide octahydrate in a molar ratio of Sr:Ti=3:4, hydroheating at 160°C to 200°C for 4 to 12 hours, washing the reaction product with deionized water and ethanol solution, and drying to obtain strontium titanate nanowires; (2) preparing a composite electrolyte: mixing the obtained strontium titanate nanowires with an organic solvent acetonitrile, ultrasonically dispersing for 10 to 30 minutes, adding a polymer matrix of polyethylene oxide, polyvinyl acetate and lithium salt of bis(trifluoromethanesulfonyl)imide lithium, stirring for 8 to 12 hours to obtain a translucent viscous sol; pouring the obtained sol into a polytetrafluoroethylene mold, drying it naturally, and then vacuum drying it at 40 to 60° C. for 12 to 48 hours, and finally performing a hot pressing treatment to obtain a solid polymer composite electrolyte membrane; The weight proportions of the components of the polymer solid electrolyte doped with strontium titanate nanowires in step (2) are: 54 parts of polyethylene oxide, 20 parts of polyvinyl acetate, 14 parts of lithium bis(trifluoromethanesulfonyl)imide, and 4 parts of strontium titanate nanowires; The hot pressing pressure is 5 to 10 MPa, and the holding time is 5 to 10 minutes; In the step (1), the obtained sodium titanate nanowires and polyvinyl alcohol are fully dispersed and then added into the strontium hydroxide octahydrate solution.
Citation Information
Patent Citations
Method for preparing strontium titanate nanometer powder of one-dimensional structure
CN101311376A
Salt-doped polymer composite solid-state electrolyte and preparation method thereof, and lithium battery
CN110504481A